Konflik Identitas Perempuan dalam Tiga Cerpen Kalimantan Timur Tahun 1980-an - Diyan Kurniawati (Balai Bahasa Kalimantan Tengah, 2020)
This paper presents the position of female characters in three East Kalimantan short stories in the 1980s. The three short stories are